2022
DOI: 10.3389/fmolb.2022.1019447
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and inhibitors of ferroptosis in psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease that features localized or widespread erythema, papules, and scaling. It is common worldwide and may be distributed throughout the whole body. The pathogenesis of psoriasis is quite complex and the result of the interplay of genetic, environmental and immune factors. Ferroptosis is an iron-dependent programmed death that is different from cell senescence, apoptosis, pyroptosis and other forms of cell death. Ferroptosis involves three core metabolites, iron, lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…DFO is an iron chelator that inhibits ferroptosis by reducing the intracellular iron content; [ 31 ] while Fer‐1 can inhibit ferroptosis by impairing lipid peroxidation through upregulation of GPX4 and nuclear factor erythroid 2‐related factor 2. [ 32 ] As shown in Figure 4B,C and Figure S2A,B, Supporting Information, both DFO and Fer‐1 significantly decreased the cytotoxicity of FG‐SR and FG‐STR in MC38 and B16F10 cells. Moreover, TEM revealed that compared with the control group (serum‐free medium, Figure 4D), MC38 cells in the FG‐STR‐treated group exhibited mitochondrial volume reduction with enhanced mitochondrial membrane density and disappearance of mitochondrial cristae, which were reported to be the morphological characteristics of mitochondria during erastin‐induced ferroptosis.…”
Section: Resultsmentioning
confidence: 91%
“…DFO is an iron chelator that inhibits ferroptosis by reducing the intracellular iron content; [ 31 ] while Fer‐1 can inhibit ferroptosis by impairing lipid peroxidation through upregulation of GPX4 and nuclear factor erythroid 2‐related factor 2. [ 32 ] As shown in Figure 4B,C and Figure S2A,B, Supporting Information, both DFO and Fer‐1 significantly decreased the cytotoxicity of FG‐SR and FG‐STR in MC38 and B16F10 cells. Moreover, TEM revealed that compared with the control group (serum‐free medium, Figure 4D), MC38 cells in the FG‐STR‐treated group exhibited mitochondrial volume reduction with enhanced mitochondrial membrane density and disappearance of mitochondrial cristae, which were reported to be the morphological characteristics of mitochondria during erastin‐induced ferroptosis.…”
Section: Resultsmentioning
confidence: 91%
“…These results showed that GSH At present, the process of ferroptosis is blocked mainly from four aspects: complexation of phosphate with Fe 2+ , chelation with Fe 2+ , antioxidation, and antiferroptosis. 42,43 Iron is among the most active minerals in soil and sediment, which has a strong adsorption capacity for inorganic and organic phosphate compounds. 44 Adenosine triphosphate (ATP), adenosine diphosphate (ADP), and tris(2-carboxyethyl) phosphine (TCEP) have been proved to be able to adsorb iron, resulting in a deficiency of iron, which is indispensable in ferroptosis, and thereby inhibiting ferroptosis and weakening the bactericidal effect.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroptosis is driven by increased cellular iron load and is characterized by the loss in membrane integrity and changes in mitochondrial ultrastructure, including reduced mitochondrial volume, increased mitochondrial bilayer membrane density, decreased mitochondrial cristae, and ruptured mitochondrial membrane ( Doll et al, 2017 ; Du et al, 2022 ; Zhou et al, 2022 ). Ferroptosis can be induced through the interaction of iron regulation, lipid metabolism, and ROS biology, and research in these fields is expected to deepen the mechanistic understanding, biological significance, and clinical therapeutic relevance of ferroptosis ( Table 1 ).…”
Section: Mechanisms Underlying Ferroptosismentioning
confidence: 99%